Dental patients’ awareness on effects of smoking and patients’ perception on the role of dentists in smoking cessation activities / Norashikin Yusof … [et al.] - Yusof, Norashikin; Nik Mohd Kamil, Nik Nur Adleena; Mohammad Kazmin, Najwa; Md Sabri, Budi Aslinie (2019)
This study aims to assess the awareness of patients towards effects of smoking on their general and oral health and their perception towards the role of dentists in smoking cessation activities. Methodology: Study population consists of 114 patients chosen through convenient sampling for a period of six months. Self-administered questionnaires on knowledge of impact of smoking on health and role of dentists in smoking cessation, were distributed and collected within the same visit. Descriptive statistics and Chi-square test were used to analyze the data. Results: The results showed that education level did not have significant effect on smoking status (p > 0.05). More than 90% of the respondents were aware of the effect of smoking on their general health. Both smokers and non-smokers showed positive attitude towards dentists’ role in smoking cessation activities.